1991
DOI: 10.1038/bjc.1991.341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cycloheximide on B-chronic lymphocytic leukaemic and normal lymphocytes in vitro: induction of apoptosis

Abstract: Summary A number of reports indicate that protein synthesis is a requirement for the occurrence of apoptosis. In this study, the effect of the protein synthesis inhibitor cycloheximide (CHM) on spontaneous apoptosis of B-chronic lymphocytic leukaemia (B-CLL) cells, previously shown to occur when they are cultured in RPMI-1640 medium with autologous or heterologous serum, was examined. No definite inhibition of apoptosis was observed. Indeed, CHM-treatment augmented apoptosis in the B-CLL cultures and also indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 27 publications
4
29
0
Order By: Relevance
“…At concentrations > 1 lLM we found it to induce significant (> 50% by 48 h) apoptosis, as has been reported by others (Collins et al, 1991). We found that concentrations less than 1 ,IM for 48 h did not induce apoptosis.…”
Section: Kinetics Of Dexamethasone-induced Apoptosissupporting
confidence: 72%
“…At concentrations > 1 lLM we found it to induce significant (> 50% by 48 h) apoptosis, as has been reported by others (Collins et al, 1991). We found that concentrations less than 1 ,IM for 48 h did not induce apoptosis.…”
Section: Kinetics Of Dexamethasone-induced Apoptosissupporting
confidence: 72%
“…However, the latter study has added actinomycin D and cycloheximide to the cell culture before the assay of TNF-␣-induced apoptosis. Since both actinomycin D 43,44 and cycloheximide [45][46][47] have been reported to be apoptosisinducing agents, this made their data difficult to interpret. Moreover, the enhancement of TNF-␣-induced apoptosis by HCV core protein is clearly inconsistent with the clinicopathological observations in hepatitis C patients that exacerbations are not often found in the natural history.…”
Section: Discussionmentioning
confidence: 80%
“…The fact that several disparate inducers of apoptosis, which probably act by di erent mechanisms (Boix et al, 1998), all lead to the loss of eIF4G indicates that the pathways activated by these agents converge on this target protein. Low serum conditions activate apoptosis in immortalized or transformed cell lines (Kulkarni and McCulloch, 1994;Wang and Pandey, 1995;Kawanishi, 1997), probably by depriving the cells of growth factors necessary to promote cell cycle progression (Ohta et al, 1997); cycloheximide is also an e cient inducer of apoptosis in a variety of cell types, perhaps because it blocks the synthesis of one or more proteins essential for the prevention of apoptosis (Martin et al, 1990;Collins et al, 1991;Ledda-Columbano et al, 1992;Ishii et al, 1997); the CD95 (Fas) receptor acts by binding a number of proteins to the`death domain' located on its intracellular portion; etoposide interacts with DNA topoisomerase II and induces DNA strand breaks. The point of convergence of these pathways at the level of eIF4G is most likely the activation of one or more`executioner' caspases (Longthorne and Williams, 1997; Kamada et al, 1997;Cohen, 1997).…”
Section: Discussionmentioning
confidence: 99%